Oxidative Stress and Inflammatory Status in COVID-19 Outpatients: A Health Center-Based Analytical Cross-Sectional Study - Sahar Golabi; Sheyda Ghasemi; Maryam Adelipour; Reza Bagheri; Katsuhiko Suzuki; Alexei Wong; Maryam Seyedtabib; Mahshid Naghashpour (MDPI AG, 2022)
The antioxidant system can be critical in reducing exacerbated inflammation in COVID-19. This study compared the antioxidant and inflammatory responses between COVID-19 outpatients and seemingly healthy individuals. This descriptive-analytical cross-sectional study was conducted on 53 COVID-19 outpatients and 53 healthy individuals as controls. The serum concentrations of amyloid A (SAA), total antioxidant capacity (TAC), superoxide dismutase (SOD), and glutathione peroxidase (GPx) were measured and compared between COVID-19 patients and controls using the independent sample t-test before and after controlling for dietary supplement use. A generalized estimating equation (GEE) regression model, limited to COVID-19 patients, was used to evaluate the odds ratios (ORs) and 95% confidence intervals (95% CIs) of disease symptoms on days 1, 7, 14, 21, and 28 after the disease onset. Serum concentrations of SOD (p ≤ 0.001) and GPx (p = 0.001) were significantly higher in COVID-19 patients than in controls before adjustment for dietary supplement use. GPx remained significantly higher among COVID-19 patients than in controls after adjustment for all dietary supplements (p = 0.005). Moreover, serum concentrations of GPx (p = 0.003), SOD (p = 0.022), and TAC (p = 0.028) remained significantly higher among COVID-19 patients than in controls after adjustment for vitamin D supplementation. This study showed higher GPx in COVID-19 outpatients than in controls after adjustment for dietary supplement use. Moreover, elevated SOD, GPx, and TAC concentrations were shown in COVID-19 outpatients compared to controls after adjusting for vitamin D supplementation. These results may provide a useful therapeutic target for treating oxidative stress in COVID-19 disease, which may help ameliorate the pandemic.